2003
DOI: 10.1590/s0100-879x2003000800007
|View full text |Cite
|
Sign up to set email alerts
|

Thymocyte migration: an affair of multiple cellular interactions?

Abstract: Cell migration is a crucial event in the general process of thymocyte differentiation. The cellular interactions involved in the control of this migration are beginning to be defined. At least chemokines and extracellular matrix proteins appear to be part of the game. Cells of the thymic microenvironment produce these two groups of molecules, whereas developing thymocytes express the corresponding receptors. Moreover, although chemokines and extracellular matrix can drive thymocyte migration per se, a combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 37 publications
0
19
0
1
Order By: Relevance
“…It has been well defined that ligands and receptors of ECM and chemokines as well as adhesion molecules are involved in T-cell migration events [5,16,17,[36][37][38][39]. However, little is known about the influences of hormone in this process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well defined that ligands and receptors of ECM and chemokines as well as adhesion molecules are involved in T-cell migration events [5,16,17,[36][37][38][39]. However, little is known about the influences of hormone in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have shown that cell-ECM interactions seem to be dependent on integrin surface expression, ECM deposition and degradation [15][16][17]. Furthermore, in vivo stimulation of lymphocyte migration and positioning within tissues seems to occur with chemokines and ECM components acting conjointly [18][19][20][21]41].…”
Section: Introductionmentioning
confidence: 99%
“…In this vein, it has been shown that TEC are sensitive to fluctuations in laminin: TEC grow faster onto a laminin substrate [55], which also enhances the expression of focal adhesion kinases by these cells [50,51] and augment IL-6 production through a p38 mitogen-activated protein kinase-mediated signaling cascade [56].…”
Section: Ecm Receptors In the Thymus: The Vla Familymentioning
confidence: 99%
“…Last, thymocyte exit to the periphery may also be influenced by VLA-mediated interactions; intrathymic injection of RGDcontaining peptide (recognized by the ␣5␤1/VLA-5 fibronectin receptor) results in a decreased homing of recent thymic emigrants [51]. [55,58,59]), as compared with controls, culture medium alone, or bovine serum albumin (BSA).…”
Section: Ecm Receptors In the Thymus: The Vla Familymentioning
confidence: 99%
“…The thymic microenvironment also influences thymocyte differentiation via cytokines, chemokines, adhesion molecules and extracellular matrix (ECM), most of which modulate not only differentiation but also thymocyte migration patterns [2,3] . The thymic epithelial cell (TEC) network is the major component of the thymic microenvironment, being responsible for positive selection of thymocytes, and for the production of cytokines, chemokines and various ECM components [3] .…”
mentioning
confidence: 99%